2015
DOI: 10.1016/j.foodqual.2015.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Sensory cut-off point obtained from survival analysis statistics

Abstract: In the present work we applied interval-censored survival analysis techniques to estimate sensory cut-off points based on consumer's decision to accept or reject food products taking into account the inherent variability in sensory measurements. We compared the values obtained using this survival analysis methodology with those obtained by applying a previous regression based method. Cut-off point (COP) estimations were made for acid flavor in yogurt, strawberry flavor in a strawberry flavored drink and appear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 18 publications
1
6
0
1
Order By: Relevance
“…Ot is important to perceive the acceptability profile decrease with storage time, showing a consistence with literature (Cruz et al, 2010;Garitta et al, 2015). Comi et al (2015) found 12 days for commercial beef burgers.…”
Section: Copsupporting
confidence: 74%
See 1 more Smart Citation
“…Ot is important to perceive the acceptability profile decrease with storage time, showing a consistence with literature (Cruz et al, 2010;Garitta et al, 2015). Comi et al (2015) found 12 days for commercial beef burgers.…”
Section: Copsupporting
confidence: 74%
“…From the level of rancidity indicated by the trained panel and the overall acceptability of the samples given by the assessors, the value where the acceptability of the product began to significantly decrease was calculated trough Equation 1 (Garitta et al, 2015;Hough & Fiszman, 2005): Using the proposed S value, a graph displayed the results of the assessors (overall acceptability) versus those of the trained panel (rancidity intensity). From this graph, and replacing the value for S in the equation, the X acquired was the value of the maximum acceptable rancidity.…”
Section: Cut-off Point (Cop)mentioning
confidence: 99%
“…Since we expected to maintain the sensory attributes of the products during storage as similar as possible to those of the fresh product (at the beginning of storage), the best sensory attributes were directly related to the best scores, namely the closest to the maximum score for overall appearance, odor, flavor and texture, and the closest to the minimum score for browning and red color of the juice. Although previous reports have considered the score in the middle of the scale as a limit score (Martínez et al 2005;Piagentini et al 2005), the use of nonarbitrary cutoff points was recommended (Hough and Garitta 2012;Garitta et al 2015).…”
Section: Sensory Analysismentioning
confidence: 99%
“…Thus, survival analysis may represent more clearly the expectations of consumers with respect to a product. This methodology taps directly into consumer experience (Esmerino et al., 2015; Garitta & Hough, 2012a; Garitta et al., 2015).…”
Section: Resultsmentioning
confidence: 99%